2010
DOI: 10.1177/0193945910379217
|View full text |Cite
|
Sign up to set email alerts
|

Fall Prevention Practices in Adult Medical-Surgical Nursing Units Described by Nurse Managers

Abstract: The purpose of this article was to describe nursing practices (e.g., assessment, interventions) around fall prevention, as perceived by nurse managers in adult, medical-surgical nursing units. One hundred forty nurse managers from 51 hospitals from across the United States participated. Descriptive frequencies are used to describe nurse manager responses. The most commonly used fall risk assessment tool was the Morse Fall Risk Assessment Tool (40%). The most common fall prevention interventions included bed al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 22 publications
0
20
1
Order By: Relevance
“…They moved patients into rooms closer to the nurses’ station or used sitters. Recent research has identified the use of sitters as a common strategy used within the acute care setting to prevent falls (Shever et al. , 2011).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They moved patients into rooms closer to the nurses’ station or used sitters. Recent research has identified the use of sitters as a common strategy used within the acute care setting to prevent falls (Shever et al. , 2011).…”
Section: Resultsmentioning
confidence: 99%
“…They moved patients into rooms closer to the nurses' station or used sitters. Recent research has identified the use of sitters as a common strategy used within the acute care setting to prevent falls (Shever et al, 2011). Sitters are either volunteers or paid staff, licensed or unlicensed, used to stay with patients at high risk of injury or falls (Tzeng, 2007).…”
Section: Confusion Is Normalmentioning
confidence: 99%
“…Another demographic factor that might be the reason for communication gap was that majority of nurse were from Philippine and Malaysia who were not fluent in Arabic. Another shortcoming was found in the medical curriculum because majority of nurse had bachelor degree, however about 60% did not received FP training [4][5][6][7][8][9][10].…”
Section: Discussionmentioning
confidence: 99%
“…In relation to nursing practice related to FP, color coding was found to be a major intervention for preventing fall and they also wanted improvement in FP policies. There is a need to give more power and autonomous role to nurses to prevent falls and maximize health and safety of patients during hospital stay [10][11][12][13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…Movement alarms are one of the most commonly used fall prevention strategies in hospitals (Shever, Titler, Lehan Mackin, & Kueny, ). However, movement alarms were never designed to prevent falls, rather they serve as an early warning signal that a patient is starting to get up from a bed or chair.…”
Section: Evidence Framework For Selection Of Interventionsmentioning
confidence: 99%